Decreased serum NCAM is positively correlated with hippocampal volumes and negatively correlated with positive symptoms in first-episode schizophrenia patients. (December 2020) - An, Huimei; Qin, Jun; Fan, Hongzhen; Fan, Fengmei; Tan, Shuping; Wang, Zhiren; Shi, Jing; Yang, Fude; Tan, Yunlong; Huang, Xu-Feng
Abstract: Background: Neural cell adhesion molecule (NCAM) plays an important role in neurodevelopmental processes and regulates hippocampal plasticity. This study investigated the relationship between the serum NCAM concentrations and hippocampal volume and psychotic symptoms in first-episode drug naïve schizophrenia (FES) patients. Methods: Forty-four FES patients and forty-four healthy controls (HC) were recruited in this study. Serum concentrations of NCAM were measured by ELISA. Psychiatric symptoms were assessed by the positive and negative syndrome scale (PANSS). Brain structural images were obtained using a 3T MRI Scanner and obtained T1 images were processed in order to determine hippocampal grey matter volumes. Results: Schizophrenia patients revealed significantly decreased serum NCAM concentrations ( p  = 0.017), which were positively correlated with the left (r = 0.523, p  < 0.001) and right (r = 0.449, p  = 0.041) hippocampal volumes, but negatively correlated with the PANSS positive symptom scores (r = −0.522 p  = 0.001). However, no such correlations existed in the HC group. Conclusions: This is the first time to report that decreased serum NCAM concentrations were associated with hippocampal volumes and symptom severity in FES patients. Our data indicate that the low NCAM is possible neuropathology that is associated with the decreased hippocampus in FES patients.